2019
DOI: 10.1002/jbm.a.36721
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the pectin hydrogels and inflammation response to their subcutaneous implantation

Abstract: We studied the influence of the mechanical properties of pectin hydrogels on acute inflammation and tissue repair after subcutaneous implantation. We used hard and soft pectin hydrogels. The results of histology and the analysis of serum‐level cytokines demonstrated that the intensity of acute inflammation increased with increasing hardness of the pectin hydrogels. We also showed that the pectin hydrogels did not inhibit tissue repair. The results of the morphometric and texture analysis of the pectin hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Bare polyethylene hydrogels have been proven to not exhibit cytotoxicity in murine models even after 60 days when injected subcutaneously [184]. Similar results regarding biocompatibility were obtained with ellagic acid hydrogels [185], nano-patterned poly-acrylamide hydrogels [186] chitosan and gelatin hydrogels [187,188], alginate [189] and pectin [190]. It is worth mentioning that the majority of the studies do report mild inflammatory responses.…”
Section: Hydrogel Administrationmentioning
confidence: 72%
“…Bare polyethylene hydrogels have been proven to not exhibit cytotoxicity in murine models even after 60 days when injected subcutaneously [184]. Similar results regarding biocompatibility were obtained with ellagic acid hydrogels [185], nano-patterned poly-acrylamide hydrogels [186] chitosan and gelatin hydrogels [187,188], alginate [189] and pectin [190]. It is worth mentioning that the majority of the studies do report mild inflammatory responses.…”
Section: Hydrogel Administrationmentioning
confidence: 72%
“…This observation is the most important because liver damage usually results from the toxic components of polymeric, implanted biomaterial [ 19 ]. Markov et al [ 20 ] evaluated the biocompatibility of 1% and 4% hydrogel implanted into Wistar albino rats. Similar to our findings, the researchers reported no significant changes in the histological structure of the liver, kidney, spleen, or lung.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is the most important because liver damage usually results from the toxic components of polymeric, implanted biomaterial [19]. Markov et al [20] evaluated the biocompatibility…”
Section: Discussionmentioning
confidence: 99%
“…subcutaneously implanted pectin hydrogels of diverse stiffnesses resulting from different pectin solution concentrations in rats and found that soft pectin hydrogels prepared from 1% pectin solution displayed a low proinflammatory response. [ 56 ] This might be due to a more compatible mechanical property with surrounding tissues and a reduced release of degradation products to surrounding tissues compared to pectin hydrogel made from 4% pectin solution. For PEG hydrogels, more robust neutrophil infiltration during 1–3 weeks postinjury, or chronic inflammation, was observed on stiffer hydrogels.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%